Albert Camus, The stranger - McCarthy, Patrick 1941-2007 (Landmarks of world literature, 2004)
This handy guide places Albert Camus' The Stranger, one of the seminal texts of existentialism and twentieth-century literature in general, in the context of French and French-Algerian history and culture. In it, Patrick McCarthy examines the way the work undermines traditional concepts of fiction. In addition, he explores the parallels and the contrasts between Albert Camus's work and that of Jean-Paul Sartre. Overall, this account provides students with a useful companion to The Stranger. This second edition boasts a revised guide to further reading and a new chapter on Camus and the Algerian War